2015
DOI: 10.1111/aas.12641
|View full text |Cite
|
Sign up to set email alerts
|

Association between sensory dysfunction and pain 1 week after breast cancer surgery: a psychophysical study

Abstract: Pain was increased in patients having larger areas of hypoaesthesia and reduced in patients where ICBN-section was done. Sensory dysfunction was related to extent of axillary surgery, but not with ICBN handling. Our data suggest that acute pain after breast cancer surgery may be related to nerve injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(51 citation statements)
references
References 28 publications
(38 reference statements)
2
49
0
Order By: Relevance
“…Our searches identified 189 potentially relevant studies, of which 41 full text reports were examined ( Figure 1). A total of 18 studies met the eligibility criteria ( Figure 1) (Andersen, Duriaud, Aasvang, & Kehlet, 2016;Andriamamonjy, Delmotte, Savinelli, Beaussier, & Coudore, 2017;Attal et al, 2009;Binder et al, 2007;Boyette-Davis et al, 2013, 2011aCaraceni et al, 2008;Cata et al, 2007;Dougherty, Cata, Burton, Vu, & Weng, 2007;Dougherty, Cata, Cordella, Burton, & Weng, 2004;Fallon et al, 2015;Forsyth et al, 1997;Hershman et al, 2011;Krøigård et al & Fallon, 2012;Velasco et al, 2015;Ventzel et al, 2017). Three studies included patients with tumour-related cancer pain (Andersen et al, 2016;Lipton et al, 1991;Scott et al, 2012).…”
Section: Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Our searches identified 189 potentially relevant studies, of which 41 full text reports were examined ( Figure 1). A total of 18 studies met the eligibility criteria ( Figure 1) (Andersen, Duriaud, Aasvang, & Kehlet, 2016;Andriamamonjy, Delmotte, Savinelli, Beaussier, & Coudore, 2017;Attal et al, 2009;Binder et al, 2007;Boyette-Davis et al, 2013, 2011aCaraceni et al, 2008;Cata et al, 2007;Dougherty, Cata, Burton, Vu, & Weng, 2007;Dougherty, Cata, Cordella, Burton, & Weng, 2004;Fallon et al, 2015;Forsyth et al, 1997;Hershman et al, 2011;Krøigård et al & Fallon, 2012;Velasco et al, 2015;Ventzel et al, 2017). Three studies included patients with tumour-related cancer pain (Andersen et al, 2016;Lipton et al, 1991;Scott et al, 2012).…”
Section: Included Studiesmentioning
confidence: 99%
“…A total of 18 studies met the eligibility criteria ( Figure 1) (Andersen, Duriaud, Aasvang, & Kehlet, 2016;Andriamamonjy, Delmotte, Savinelli, Beaussier, & Coudore, 2017;Attal et al, 2009;Binder et al, 2007;Boyette-Davis et al, 2013, 2011aCaraceni et al, 2008;Cata et al, 2007;Dougherty, Cata, Burton, Vu, & Weng, 2007;Dougherty, Cata, Cordella, Burton, & Weng, 2004;Fallon et al, 2015;Forsyth et al, 1997;Hershman et al, 2011;Krøigård et al & Fallon, 2012;Velasco et al, 2015;Ventzel et al, 2017). Three studies included patients with tumour-related cancer pain (Andersen et al, 2016;Lipton et al, 1991;Scott et al, 2012). Fifteen studies included patients with chemotherapy induced peripheral neuropathy (CIPN) (Andriamamonjy et al, 2017;Attal et al, 2009;Binder et al, 2007;Boyette-Davis et al, 2013, 2011aCaraceni et al, 2008;Cata et al, 2007;Dougherty et al, 2007Dougherty et al, , 2004Fallon et al, 2015;Forsyth et al, 1997;Hershman et al, 2011;Krøigård et al, 2014;Velasco et al, 2015;Ventzel et al, 2017).…”
Section: Included Studiesmentioning
confidence: 99%
“…Damage to the ICBN is associated with significant morbidity and is believed to be involved with postoperative pain and sensory loss [1, 9-10]. …”
Section: Discussionmentioning
confidence: 99%
“…It has been estimated that between 10-60% of breast cancer survivors who have undergone operative procedures, experience PPBCT, and it is believed that this predominantly neuropathic pain contributes significantly to a reduced quality of life following breast cancer treatment [1, 9-10]. Aside from dysesthesia, paresthesia of the ICBN, sensory distribution is also very common [11].…”
Section: Introductionmentioning
confidence: 99%
“…Others have demonstrated enhanced sensitivity to electrical and thermal stimulation [53, 54], further supporting the presence of central sensitization in persistent pain after breast cancer treatment. Recently, Andersen et al found a relationship between sensory disturbances and pain one week after surgery for breast cancer [55]. Hyperalgesia has also been reported 5 days after back surgery [56] and early postoperative hyperalgesia has been linked to persistent pain development in smaller studies after abdominal surgery [57, 58].…”
Section: Discussionmentioning
confidence: 99%